2008
DOI: 10.1175/2007jas2463.1
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Level Circulation in the Tropics

Abstract: Deep convective tropical systems are strongly convergent in the midtroposphere. Horizontal wind measurements from a variety of rawinsonde arrays in the equatorial Pacific and Caribbean are used to calculate the mean dynamical divergence profiles of large-scale arrays (Ն1000 km in diameter) in actively convecting regions. Somewhat surprisingly, the magnitude of the midtropospheric divergence calculated from these arrays is usually small. In principle, the midlevel convergence of deep convective systems could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The left panel highlights the main convective outflow level near ∼12 km, with the strongest closed circulation of the anticyclone somewhat above this level (∼12-16 km; Randel and Park, 2006). The mechanism(s) of vertical transport above 12 km are a subject of ongoing research, but likely involve large-scale circulation in the anticyclone , overshooting deep convection (Dessler and Sherwood, 2004), or the dynamical divergence mechanism discussed in Folkins et al (2007). Although the detailed mechanism(s) leading to formation and maintenance of the tracer profiles are not understood at present, the ACE-FTS data provide detailed observations to test idealized or more realistic models.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The left panel highlights the main convective outflow level near ∼12 km, with the strongest closed circulation of the anticyclone somewhat above this level (∼12-16 km; Randel and Park, 2006). The mechanism(s) of vertical transport above 12 km are a subject of ongoing research, but likely involve large-scale circulation in the anticyclone , overshooting deep convection (Dessler and Sherwood, 2004), or the dynamical divergence mechanism discussed in Folkins et al (2007). Although the detailed mechanism(s) leading to formation and maintenance of the tracer profiles are not understood at present, the ACE-FTS data provide detailed observations to test idealized or more realistic models.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Their constructed deep convective life cycle is marked by cooling in the lower to mid troposphere, warming in the mid to upper troposphere, and cooling at TTL altitudes. More recently, Folkins et al (2008) and Mitovski et al (2010) successfully revealed similar local convective temperature signals associated with high rainfall rates from the Tropical Rainfall Measuring Mission (TRMM) at tropical radiosonde stations. These earlier studies were limited by (1) using proxies for deep convective clouds (brightness temperature, rain rate), (2) the limited spatial coverage given by the small number of radiosonde station locations.…”
Section: Introductionmentioning
confidence: 94%
“…However, with the exception of van den Heever et al (2011), previous studies did not specifically address how aerosols (serving as CCN) affected the frequencies of cumulus congestus. Nevertheless, congestus are an important component of tropical convection (e.g., Johnson et al 1999;Folkins et al 2008). Recent studies have emphasized their crucial role in moistening mid-troposphere, setting up the optimal condition for deep convective systems, especially in the context of the Madden̶Julian oscillation (MJO) lifecycle (Kemball-Cook and Wearethe cumulus congestus population over the tropical oceans have been studied by Johnson et al (1996), Mapes and Zuidema (1996), Folkins et al (2008), and Folkins et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, congestus are an important component of tropical convection (e.g., Johnson et al 1999;Folkins et al 2008). Recent studies have emphasized their crucial role in moistening mid-troposphere, setting up the optimal condition for deep convective systems, especially in the context of the Madden̶Julian oscillation (MJO) lifecycle (Kemball-Cook and Wearethe cumulus congestus population over the tropical oceans have been studied by Johnson et al (1996), Mapes and Zuidema (1996), Folkins et al (2008), and Folkins et al (2009). These factors include the relatively small convective available potential energy (CAPE) and the weak stable layer around the melting layer, which is sometimes accompanied by a dry air layer.…”
Section: Introductionmentioning
confidence: 99%